Avaliação da eficiência do complexo ferricitrato como indutor da reação foto-fenton para o tratamento de lixiviados de aterros sanitários - Zorzo, Camila Fernanda (2016)
This work had the objective to evaluate the efficiency complex formed between citric acid and ferric ions (ferricitrate) as inductor photo-Fenton reaction to the treatment of landfill leachate. The samples of leachate were collected at the Regional Center of Solid Waste Treatment, in the city of Giruá (RS). This leachate is characterized to present high color and turbidity, as well as elevated organic content expressed in high values chemical and biochemical oxygen demand (COD and BOD 5 ), total organic carbon (TOC), nitrogen forms and phosphor, with high pollution potential. The use of organic ligand aims to improve the efficiency of the photo-Fenton process, since that form stable and soluble complexes with Fe (III), and possible reactions the a higher pH than traditional. To study the kinetics was used a lab-scale photoreactor equipped with mixed lamps of mercury (3x500 W), a German borosilicate reactor (Schott-Duran 3.3, cutoff 280 nm) with an internal diameter of 46,4 mm, length 180 mm and thickness of 1,8 mm, positioned on concentrator parabolic collector (CPC) with reflectors electropolished anodized aluminum, peristaltic pump at a flow rate of 630 mL min -1 , pHmeter and magnetic stirrer. The main operational parameters evaluated are adjusting the pH of the solution, the addition of catalytic iron ions and hydrogen peroxide, making as response variables the reduction of aromatic compounds and discoloration of the leachate. Too there was the statistical analysis of data collected in the experiments. The best results were achieved at pH 5,0 and 7,8 with a ferric ion concentration of 90 mg Fe L -1, obtaining ≈40% reduction of aromatic compounds and ≈20% color. In these conditions there also greater reduction of concentration of dissolved iron and low precipitation of humic acids in the acidification step.